Gene Polymorphism of Vitamin D Receptor (VDR) in Iraqi Population - Khulood K. Hasan (Journal of Global Pharma Technology, 2019)
Vitamin D receptor (VDR) gene has several variants.The distribution of these polymorphisms may vary among different ethnic groups therefore in this paper; we seek to determine population frequencies of selected VDR polymorphisms (FokI rs2228570 and TaqI rs731236) in the healthy Iraqi population. Genotyping for two VDR single nucleotide polymorphism were performed for a total of sixty healthy individuals using Polymerase Chain Reaction- Restriction Fragment Length Polymorphism (PCR-RFLP). For FokI polymorphism, genotypes frequencies were 70%, 26.6% and 3.3% for FF, Ff and ff respectively and 50%, 45 % and 5% for TT, Tt and tt genotype for TaqI polymorphism respectively. As for the Allelic frequencies, the readings were 83.3 % opposed to 16.6 % for F and f alleles and 72.5 % opposed to 27.5 % for T and t alleles. In addition, the pattern regarding distribution of FokI and TaqI genotypes and alleles in the Iraqi Arab population was different from other ethnic groups. VDR polymorphisms data distribution among the healthy population in this work can be capitalized to investigate possible associations of VDR gene with different diseases. Further, anthropological comparisons can be attained using the same data set.Keywords: Vitamin D receptor, VDR polymorphism, VDR SNPs.